Mega-Events and Geopolitical Communication: Arab and Global North Strategies of Visibility and Soft Power - Dr. Tommy Kibera Kiilu (LSPR Institute of Communication & Business, 2026)
Mega-events have evolved from cultural and sporting gatherings into sophisticated instruments of geopolitical communication and soft power. In an era of mediated global politics, states use these high-profile spectacles to shape international perception, construct legitimacy, and project national influence. This study aims to compare how Arab and Global North nations deploy mega-events as strategic platforms for visibility and narrative control within global hierarchies of power. Using a comparative case study method, it examines Arab cases—Qatar’s 2022 FIFA World Cup, Expo 2020 Dubai, and Saudi Arabia’s Expo 2030 bid—alongside Western counterparts such as the London 2012 Olympics, the Venice Biennale, and Paris 2024 Olympics. The analysis draws on framing theory, soft power theory, and critical geopolitics to interpret how event communication and media representation operate as geopolitical performance. Findings reveal that Arab states employ mega-events to counter stereotypes, enhance legitimacy, and reposition themselves as global mediators, while Western nations use them to reassert cultural authority and sustain leadership narratives in a changing world order. The paper concludes that mega-events are not neutral cultural displays but symbolic battlegrounds for visibility, legitimacy, and influence in a media system structured by enduring global asymmetries. These insights advance Arab media and global communication scholarship by situating mega-events as dynamic arenas of soft power negotiation.